True-Time-Delay-Based Fast Beam Training for Millimeter-Wave Communication Systems - Zhou, Liang; Dateki, Takashi (IEEE Vehicular Technology Conference, 2021)
Millimeter-wave (mmWave) communications rely on beamforming gain for both transmitters (TX) and receivers (RX) to overcome high propagation loss. To achieve adequate array gain, beam training is required to identify propagation directions and reduce interferences, which is one of the most important and challenging tasks in mmWave communications. To avoid prohibitive beam training overhead with large antenna arrays and narrow beams, this paper presents two fast true-time-delay (TTD) arrays-based algorithms for both TX and RX beam training. TTD arrays can provide frequency-dependent beam steering in parallel. Based on this fact, the proposed training algorithms with TTD architecture use different subcarriers in one orthogonal frequency division multiplexing (OFDM) symbol to steer different beam directions simultaneously. Simulation results show that the proposed algorithms with multiple beam candidates can achieve a high-accuracy estimation of TX and RX beam patterns while requiring an order-of-magnitude fewer training symbols than those of phased antenna arrays (PAA).